UPAYA MAHASISWA KKN DALAM PROGRAM PENDIDIKAN NON-FORMAL DI MASJID AL-IKHLAS DESA SUMBER MAKMUR - Furoidah, Nadzrotul; Natalia, Desti Fitriani; Wulandari, Wulandari; Sari, Fifi Anita Dila; Boma, Hutra; Pramestie, Dea Rizqina; Hermakoy, Zeny; Sarjono, Jebby; Ramansyah, Dendi (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Student Community Service (KKN) is an important part of the Tri Dharma of Higher Education that focuses on community service. The KKN program at the Al-Ikhlas Mosque, Sumber Makmur Village, is an example of the application of this concept with the main objective of improving the quality of non-formal education in the village. This study examines the efforts of KKN students in implementing a non-formal education program that includes religious education and life skills, using participant observation methods, in-depth interviews, and document analysis. Data were collected from KKN students, program participants, and community leaders to obtain a comprehensive picture of the program's implementation. The results of the study showed that this program had a significant positive impact. The increase in religious knowledge and life skills was seen from the active participation of residents in the activities held, as well as the building of a sense of togetherness and concern for the community. However, the study also noted the need for increased cooperation with the village government and the use of technology to expand the reach of the program. With the implementation of these recommendations, future KKN programs are expected to provide greater and more sustainable benefits to the community. The program at the Al-Ikhlas Mosque has succeeded in achieving its expected goals and has made a positive contribution to improving the knowledge and skills of the village community.